Revealing Awareness and Compliance of Tax - Khoirul Fuad; Lutfi Khusfiyah (Journal of Applied Accounting and Taxation, 2019)
This study aims to determine the empirical evidence of tax knowledge, trust, transparency an tax awareness to tax compliance. This study involved 100 respondents as samples using accidental sampling technique. Respondents who participated in this study were the WPOP and the WP Badan registered at KPP Pratama Jepara. This type of research is quantitative method using primary data. In this study, data was collected by distributing questionnaire for 5 days. The data in this study were analyzed with Partial Least Square (PLS) using Smart PLS 3.0 software.The result showed that there are two variables which are tax knowledge and transparency has posoitive significant effect toward tax awareness and tax compliance. Although, there are still variables which don’t have any significant effect. The variables is tax awareness toward tax compliance, trust toward tax awareness and trust toward tax compliance. Tax awareness does moderating effect of tax knowledge and transparency on tax compliance. Tax awareness doesn’t have mediating effect of trust toward tax compliance